Estudio de factibilidad para la creación de una empresa comercializadora de alarmas de seguridad en el cantón La Maná, año 2013. - Alcaciega Guanin, Veronica Elizabeth (2014)
The present research is to create a trading company security alarms, contributing to the prevention of illegal activities in the Canton La Maná. The aim of the research is to obtain a survey of relevant, specific and general market of all parameters needed for installation and start-up company, as well as technical and technological feasibility, return on investment and risk assessment and benefits that may result in the project, it is intended to guide the entrepreneur to invest in the project. With an investment of economic study determined $ 53,729.57, resulting in a NPV of $ 24.683.67, a yield of 28% and a payback period of 2 years 8 months 16 days. It is noteworthy that the primary data collected directly from the manager and / or owners of commercial, financial and services through surveys. It tells us that customers are on average economic - social media. The percentage of market share of Canton La Maná is 92% since there are currently no place selling security alarms.